Innovative solutions for the fruition of Cultural Heritage: VALUE - Lopes et alii, Antonino (Archeomatica, 2023)
The digital revolution has helped to radically change perspective in the provisioning of goods and services in all market sectors. In the CH business, people visit's approach has substantially changed, with the introduction of new enabling technology, i.e., Artificial Intelligence and related technologies like Computer Vision, Machine Learning, eXstended Reality, etc. The digital evolution, by modifying the process of providing the cultural services, determines important changes both in the ways of using the asset and in the role of the visitor, who more often has the possibility of interacting firsthand with the cultural artworks. The VALUE project provides a different cultural fruition method, based on the use of mixed reality technologies capable of making the visit a unique emotional experience.